A facility for the research, development, and translation of advanced technologies for ion-beam therapies. (19th March 2021) - Lis, M.; Newhauser, W.; Donetti, M.; Durante, M.; Weber, U.; Zipfel, B.; Hartmann-Sauter, C.; Wolf, M.; Graeff, C.
Abstract: This article describes the updated GSI radiotherapy research facility (Cave M) located at the GSI Helmholtz Center for Heavy Ion Research in Darmstadt, Germany. This facility was upgraded by modernizing the beamline that supported a pilot project in carbon ion cancer therapy in Europe from 1997 to 2008. Descriptions are provided of the modernized beamline, related hardware components and treatment delivery system. The performance specifications and general characteristics for each major component are described, along with example pre-clinical test results of selected components. These upgrades to Cave M allow for investigating novel therapy methods. The radiotherapy research facility is located on a beamline of the heavy ion synchrotron (Schwer-Ionen-Synchrotron, or SIS-18) accelerator complex, capable of delivering 0.1 to 2 GeV/u charged particle beams, ranging from protons to uranium. This beamline contains components for fast beam gating, aborting, focusing, scanning, monitoring, and shifting the range of the beam. The beam scanning magnets, position detectors, and beam monitors are described, along with tests of functionality and performance. A dose delivery system (DDS) was adapted from a clinical unit at the National Centre for Oncological Hadrontherapy (CNAO), Pavia, Italy, and consists of modular real-time hardware and software. The DDS was modified to enable research on adaptively-managed patient motion through the use of libraries of 4D-optimized radiation treatment plans, an unsolved problem of importance for treating moving tumors. The system is modular and is designed to support future research studies, such as high dose rate (Flash) radiotherapy and radioactive ion beams. A series of validation tests confirmed the functionality and performance of various key components and systems. For example, an end-to-end test revealed that dosimetric spatial homogeneity of over 95% was achieved for square treatment fields. More generally, all performance characteristics that were tested satisfied anticipated clinical requirements.